Studi Kebiasaan Makanan Ikan Layur (Trichiurus lepturus) di Perairan Pantai Bandengan Kabupaten Jepara dan di Perairan Tawang Weleri Kabupaten Kendal - Abidin, Zaenal; Redjeki, Sri; Ambariyanto, Ambariyanto (977-2407769)
Ribbonfish as demersal fish which is one of export commodity and can be found in Java coasts and estuaries in Sumatra. This research aims to determine the food habits of ribbonfish (Trichiurus lepturus) by analyzing the types of food found in the stomach of the fish collected from coastal area of Bandengan, Jepara Regency and the waters of Tawang, Kendal, both in Central Java Province. Food habits of fish was determined by stomach content analysis. The result indicates that food type of ribbonfish (T. lepturus) from Bandengan, Jepara, mostly were anchovies, long-jawed mackarel and white snappers. While food type of fish from Tawang, Kendal, mostly were ponyfish, followed by longjawed mackarel, and anchovies. The difference of food habits probably due to biotic condition environmental differences and like temperature, light, space and surface area.